Osmoregulation performance, condition factor, and gonad maturity of tilapia (Oreochromis niloticus) in Cengklik reservoir, Boyolali - Aryansyah, Akbar; Anggoro, Sutrisno; Afiati, Norma (Universitas Malikussaleh, 2023)
Osmoregulation is a physiological adjustment mechanism of fish to environmental conditions. Fish growth performance will reduce when a large amount of energy is redirected for the osmoregulation process. The purpose of this study was to determine the osmotic work level (OWL), osmoregulation pattern, condition factor (K), gonad maturity stages (GMS) and analyze the relationship between OWL with condition factor and GMS of tilapia collected from three floating net cages in Cengklik reservoir, Boyolali. Samples were collected during March - April 2022 followed by some allometric measurements and regression analyses. The OWL of tilapia at the three cages ranged from 4 - 10 mOsm/L H2O; they performed a hyperosmotic osmoregulation pattern. The condition factor of male and female tilapia were1,86±0,21 and 1,89±0,18. GMS of both male and female tilapia was dominated by GMS IV with a fecundity of 9408±2092.54 eggs. OWL did not reveal a significant effect on condition factors or on the GMS of tilapia (p>0.05). Pearson correlation test showed a weak relationship between OWL with condition factors (r = 0,204) and tilapia GMS (r = -0,001). Therefore, tilapia uses less energy in osmotic work to produce good growth performance because it has more energy for growth, as indicated by the high condition factor (K>1) and domination by fish with GMS IV level of mature gonads.Keywords: Condition Factor; Gonad Maturity; Fish Cages; Oreochromis niloticus; Osmoregulation